The Effect of Software on Knowledge and Performance of Teenage Girls toward Puberty Hygiene: a Randomized Controlled Trial - sakineh Mohammad Alizadeh Charandabi; mojgan mirghafourvan; azad rahmani; simin seidi; elnaz safari; minoo mahini; sima saghi (مجله ایرانی آموزش در علوم پزشکی, 2014)
Introduction: Nowadays there is more inclination for using computer-based education for teenagers. With regard to the limited number of studies on the efficiency of these methods toward puberty hygiene education, this study aims to determine the effect of software on knowledge and performance of teenage girls toward puberty hygiene. Methods: This trial was carried out on 620 teenage girls who had experienced menarche and were studying in secondary school in Tabriz during 2012-2013 academic years. Twenty one randomly selected schools were paired/matched based on students' baseline performance score and were randomly and equally assigned in to the groups booklet, software, and no intervention. Using a self administered questionnaires in two stages (pre and post intervention), data on knowledge and performance were collected with one month interval. Linear regression test was used to compare post-intervention scores in three groups adjusting for the baseline scores and the cluster effect. Results: Post-intervention knowledge score in the software group was significantly higher compared to booklet group (adjusted difference 13.1) and no intervention group (adjusted difference 16.3 and p<0.001). Considering individuals’ performance score promotion, no significant difference was observed comparing software group to booklet and no intervention group. Conclusion: Findings of this study showed that software can be used for promoting knowledge of teenage girls toward puberty hygiene. However, according to study limitations and lack of software efficiency on teenagers' performance, doing further studies in this area is recommended.